PONDOK PESANTREN MODERN PUTRA DI MARTAPURA - Faeza, Muhammad Fajar; Tharziansyah, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
The design of the Modern Putra Islamic Boarding School in Martapura, South Kalimantan was based on the background of a lot of public interest today and the awareness of the importance of quality education so that the morals of every individual human being can be better and also from a general scientific perspective. Also, boarding school educators such as this pesantren can avoid most of the covid-19 virus because students do not leave the pesantren area so the need for Islamic boarding schools. The design problem raised is to create a comfortable and quiet Islamic boarding school. The problem-solving method used to create a comfortable and quiet Putra Islamic boarding school is the William M. Pena model of architectural programming. With the architectural programming method, the design will be adjusted to the needs and activity patterns of the students so that the design can help support the students' learning achievement. The design concept used is space as a learning medium by applying mass and spatial planning, comfort and tranquility, quality education, and educational concepts. Modern Islamic boarding schools are closely related to school classrooms in general. So that the classroom becomes one of the spaces that must be considered and designed according to the needs to create high-quality education. Apart from school areas, mosques (places of worship) and dormitories (rest areas) are areas that should be prioritized in this design.